Penguatan Kompetensi Guru MTs Di Ngaliyan melalui Seni Publik Speaking - Ma'mun, Nadiah (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
Good public speaking skills are absolutely necessary for teachers. Teachers are expected not only smart in the understanding of teaching materials, but also skilled in communicating, especially communication in public. With good public speaking skills they can communicate anything to the community effectively and efficiently. Thus, the community will be more able to entrust their children to be educated in Madrasah Tsanawiyah. This devotional activity is divided into two main activities, namely training on public speaking and followed by mentoring activities to teachers in Madrasah Tsanawiyah Fatahillah. This Public Speaking Training has received a very positive response from the Head of Madrasah Tsanawiyah Fatahillah and the teachers. They are eager to follow session after session of skills. After attending this public speaking training, teachers must continue to hone and train their skills, in order to increase their skill and professional in communicating with the students and the community. This training will be done continuously to support the professionalism of lecturers and community of public speaking lovers.Â Ketrampilan berbicara publik yang handal ternyata mutlak diperlukan oleh para guru. Guru diharapkan tidak sekadar pintar dalam pemahaman materi ajar, tetapi juga terampil dalam berkomunikasi, khususnya komunikasi di depan umum. Dengan ketrampilan Public speaking yang baik mereka dapat mengkomunikasikan apa saja kepada masyarakat secara efektif dan efesien. Dengan demikian, masyarakat akan lebih dapat mempercayakan anak-anak mereka untuk dididik di MTS. Pelatihan Public Speaking ini ternyata mendapat tanggapan yang sangat positif dari Ibu Kepala MTS Fatahillah dan para guru. Dan mereka bersemangat dalam mengikuti sesi demi sesi ketrampilan. Setelah mengikuti pelatihan public speaking ini, para guru harus tetap mengasah dan melatih kemampuannya, agar bertambah trampil dan profesional dalam berkomunikasi dengan para murid dan masyarakat. Pelatihan ini akan kita lakukan terus-menerus untuk menunjang profesionalisme dosen dan masyarakat pencinta public speaking.